2019
DOI: 10.1088/1361-6560/ab44ff
|View full text |Cite
|
Sign up to set email alerts
|

Fast automated multi-criteria planning for HDR brachytherapy explored for prostate cancer

Abstract: We developed a fast and fully-automated, multi-criteria treatment planning workflow for high dose rate brachytherapy (HDR-BT). In this workflow, the patient-CT with catheter reconstructions and dwell positions are imported from the clinical TPS into a novel system for automated dwell time optimisation. The optimised dwell times are then imported into the clinical TPS. The aims of automation were (1) planner-independent, enhanced plan quality, (2) short optimisation times. Our in-house developed system for full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 34 publications
(46 reference statements)
0
37
0
Order By: Relevance
“…[53,55,56]. Another approach to handle DVMs is to approximate the Heaviside step functions (corresponding to the binary indicator variables) with smooth nonlinear sigmoid functions, 6,35,[68][69][70]…”
Section: B3 Properties and Solutions Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[53,55,56]. Another approach to handle DVMs is to approximate the Heaviside step functions (corresponding to the binary indicator variables) with smooth nonlinear sigmoid functions, 6,35,[68][69][70]…”
Section: B3 Properties and Solutions Methodsmentioning
confidence: 99%
“…Also treatment plan quality can be improved with the use of optimization. 6,[31][32][33][34][35][36] In one study, 34 planners were presented with a manually constructed dose plan and five dose plans which were constructed with an optimization model. It turned out that they preferred an optimized dose plan in 53 out of 54 cases.…”
Section: B Why Use Optimization?mentioning
confidence: 99%
See 2 more Smart Citations
“…Optimization methods for dose planning have been reported to only take a few seconds, see for example [11,36], and most approaches do not require more than a few minutes to find acceptable dose plans. Secondly, several studies have shown improvements in dose plan quality compared to manual planning; see [11,36,37,38,39,40] for prostate cancer examples. Furthermore, the use of mathematical optimization also reduces the dependence of personnel skills and experience on treatment outcome.…”
Section: Why Use Optimization?mentioning
confidence: 99%